Message-efficient in-network location management in a multisink wireless sensor network. (2nd January 2008) - Lin, Chih-Yu; Tseng, Yu-Chee; Peng, Wen-Chih; Lai, Ten H.; , Hua-Wei Fang
A wireless sensor network (WSN) consists of many tiny sensor nodes. The distributed memory spaces of sensors can be considered as a large distributed database, in which one can conduct in-network data processing. This paper considers a sensor network used for object tracking where distributed location updates and queries are performed inside the network. Although this issue has been intensively studied for cellular networks, the same problem in sensor networks has very different characteristics. In this paper, we propose an efficient location management scheme for object tracking in a multisink sensor network where users can inquire the locations of objects via any sink in the network. The proposed location management scheme consists of two parts. Firstly, a message-efficient algorithm that describes how to perform location updates and queries is proposed. Secondly, two distributed virtual tree construction algorithms are also presented. The goal is to reduce the overall update and query cost. The efficiency of the proposed algorithms is evaluated and verified by simulations.